Detecting the B-mode Polarisation of the CMB with Clover - North, C; Johnson, B; Ade, P; Audley, MD; Baines, C; Battye, R; Brown, M; Cabella, P; Calisse, P; Challinor, A; Duncan, W; Ferreira, P; et al. (2008)
We describe the objectives, design and predicted performance of Clover, which is a ground-based experiment to measure the faint ``B-mode'' polarisation pattern in the cosmic microwave background (CMB). To achieve this goal, clover will make polarimetric observations of approximately 1000 deg^2 of the sky in spectral bands centred on 97, 150 and 225 GHz. The observations will be made with a two-mirror compact range antenna fed by profiled corrugated horns. The telescope beam sizes for each band are 7.5, 5.5 and 5.5 arcmin, respectively. The polarisation of the sky will be measured with a rotating half-wave plate and stationary analyser, which will be an orthomode transducer. The sky coverage combined with the angular resolution will allow us to measure the angular power spectra between 20 < l < 1000. Each frequency band will employ 192 single polarisation, photon noise limited TES bolometers cooled to 100 mK. The background-limited sensitivity of these detector arrays will allow us to constrain the tensor-to-scalar ratio to 0.026 at 3sigma, assuming any polarised foreground signals can be subtracted with minimal degradation to the 150 GHz sensitivity. Systematic errors will be mitigated by modulating the polarisation of the sky signals with the rotating half-wave plate, fast azimuth scans and periodic telescope rotations about its boresight. The three spectral bands will be divided into two separate but nearly identical instruments - one for 97 GHz and another for 150 and 225 GHz. The two instruments will be sited on identical three-axis mounts in the Atacama Desert in Chile near Pampa la Bola. Observations are expected to begin in late 2009.